My Buried Treasure - Davis, Richard Harding, 1864-1916 (Salt Lake City, UT : Project Gutenberg, 1999)
"My Buried Treasure" by Richard Harding Davis is a narrative non-fiction work written during the early 20th century. This book recounts the author's true adventure in search of buried treasure, although it cleverly refrains from revealing the true identity of his companion on the quest. The story unfolds as a humorous reflection on the eccentricities of treasure hunting and the characters involved in such pursuits, emphasizing the contrast between romantic notions of adventure and the practical realities of the undertaking. In this engaging tale, the author, who remains unnamed, teams up with a man he refers to as Edgar Powell, a cautious and methodical individual with a background in business. The plot kicks off when Edgar shares a story about a document he received from a deceased tenant, claiming it leads to buried pirate treasure. As the expedition commences, humor ensues from Edgar's desire to avoid any dangers and his meticulous planning, contrasting with the narrator's romantic view of treasure hunting. Their journey reveals a mix of absurdity and anticipation as they undertake the task of digging in search of the fabled treasure, which hilariously culminates in unexpected outcomes and reflections on the nature of such escapades. The book ultimately serves as a witty commentary on human ambition and folly in the face of alluring myths. (This is an automatically generated summary.)
Release date is 1999-05-01
Aaron Cannon and David Widger
Keywords: Fiction; Short stories